Numerical investigation of gas–liquid two-phase flow in a quench chamber of an entrained flow gasifier. (2nd March 2017) - Chai, Hongli; Geng, Fan; Wu, Xuan; Yang, Yingying; Luo, Gang; Zhang, Tiantian
Abstract: Coal gasification plays an important role in hydrogen production technologies. In this study, the processes of the syngas passing through the quench chamber were investigated for an entrained flow gasifier. First, a 3D physical model was established for the gas–liquid two-phase flow in a simplified quench chamber. The gas–liquid flow was modeled as turbulent, described by the RNG k - ε model. The interface between the liquid and the gas phases was modeled with the volume of fluid model by tracking interface of the two-phase flow in the quench chamber. Second, the flow behavior of the entrained flow was numerically investigated accompanied by some experiments. The detailed evolution of air bubbles was visually presented, including the formation, the growth and the upward movement. Third, the amount of the entraining water and the residence time for the syngas passing through the quench chamber were analyzed with the consideration of the major influences, including the air velocity, the initial water level, the interval between the ascending tube and the descending tube, and the water velocity from the cooling ring. Numerical results indicate that the major influences all have obvious effect on the flow behavior and the entraining water problem. The tendencies from the computational results were also compared with relevant experimental results, and reasonable agreements could be obtained. Moreover, the residence time for the syngas passing through the quench chamber also varies with different conditions. The present results on the entraining water provide an insight into the competing process of the gas–liquid two-phase flow in the entrained flow gasifier. Graphical abstract: The gas–liquid two-phase flow in a quench chamber of an entrained flow gasifier. Highlights: Gas–liquid two-phase flow was investigated in detail with VOF method and RNG k - ε model. Detailed information on air bubbles was validated by the present experiments. Entraining water problem and residence time of syngas were analyzed with major influences. Reasonable agreements were obtained and would provide consults for further study.